Schmidt-hammer exposure-age dating of talus slopes in upper Jostedalen, southern Norway: Interpreting the age and development of diachronous surfaces - John Matthews (The Holocene, 2025)
Schmidt-hammer exposure-age dating (SHD) was used to evaluate the surface age, dynamics and evolution of eight talus (scree) slopes located between ~520 and ~1010 m a.s.l. in the upper Jostedalen area of southern Norway. Statistically significant differences in mean R-values were found between talus slopes but there was no consistent difference in R-values between three mid- to lower-slope positions, two operators, or first and second impacts from the same boulders. A new regional age-calibration equation yielded SHD ages ranging from 8425 ± 700 years to 2620 ± 740 years. SHD ages from talus slopes and other landforms with diachronous surfaces (such as alluvial fans, snow-avalanche fans, pronival ramparts and rock glaciers) represent the average exposure age of the surface boulders and provide insights into landform evolution. Here, our SHD ages are interpreted in terms of Early Holocene paraglacial rock-slope instability, Mid-Holocene permafrost degradation, low but possibly variable rates of rockfall activity in the Late-Holocene, and spatial variations affected by local site differences. Survival of rock particles with relatively old exposure ages towards the distal margins of the talus slopes is attributed to their slow development with low levels of modern activity. SHD ages from diachronous surfaces may considerably underestimate landform age (defined as the onset of landform formation). Greater application can be anticipated, however, in the inference of landform dynamics from the R-value distributions of diachronous surfaces and in the use of SHD age as an indicator of the extent of modern activity.